Hybrid molten carbonate fuel cell and gas turbine cycle: technical analysis - Leal, ElisÃ¢ngela Martins (International Journal of Applied Power Engineering (IJAPE), 2021)
Hybrid systems that includes the use of fuel cells and thermal engines have been proposed and studied with promising results. Molten carbonate fuel cells (MCFC) present numerous advantages compatible with the current demands for the energy production in a sustainable and commercially competitive way. However, MCFC susceptibility to the deterioration of its components implies a reduced useful lifetime, being an obstacle to the potential of its economic attractiveness. This paper presents a technical analysis of the main variables on the energy efficiency and power generation of a hybrid system comprised of a molten carbonate fuel cell and a gas turbine through the determination of fuel cell design points and subsequent hybrid system modeling. Results indicate that the increase in temperature and in operating pressure of the fuel cell as well as the fuel reform rate improves the performance of the hybrid system as a whole. Variation in the utilization factor, however, did not determine an expressive increase in the system efficiency.